‘Protodesign’: The genesis of design, or a few things that changed the world - L Yu Bronzino; R A Sviridov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
The concept ‘design’ that has recently become popular in everyday discourse and among social scientists has not received an unambiguous interpretation. The ambiguity of the concept is due primarily to the complexity of the interpretation of very diverse social practices, the history of which can be traced to the earliest cultural practices of the humankind. This gives the design a universal character and exceptional significance: through the prism of this concept, we can trace the evolution of human culture as a whole. Thus, the study of the concept ‘design’ in the article is based on this theoretical background and emphasizes its basic feature - projectivity genetically related to the project thinking as an essential attribute of human activity. The logic of the article corresponds to the sequence of the main historical stages of the project thinking formation marked by specific inventions. Such an approach allows us to trace the evolution of the design revealing its genesis in the connection with the key moments of the industrial development and scientific and technological revolution as well as the most important social events that contributed to the development of the modern society urban environment and predetermined its social structure.